1999
DOI: 10.1021/jp982658t
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Interaction between Halomethanes and Water-Ice

Abstract: The infrared spectra of a series of twenty-three halogenocarbon compounds co-deposited onto water-ice held at 12 K have been investigated. Perturbations to the water (D2O) sites which are not saturated in the absence of guests show distinct trends depending on the type and extent of halogen substitution in the occluded molecules. The data are quantified in terms of the IR spectral positions of the so-called “dangling bond” of water; interaction also leads to changes in the halogenocarbon compound IR spectra. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
31
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 26 publications
7
31
1
Order By: Relevance
“…We used the standard G3 procedure [45] with the zero point energy corrected by using the HF frequency scaled by 0.8929, while Ma apparently used the MP2 frequencies scaled by 0.9661. However, our calculations (also Ma et al [39] and He and Wang's [49]) of the PAs of the chloromethanes at 298 K are significantly higher than the numbers quoted by Hunt and Andrews [57] and Holmes and Sodeau [58] who assumed a linear relationship between the frequency shift of the IR absorption (HF or D 2 O) bands for the entire chloromethane series (cold trapped in solid argon matrices with either HF, DF [57] or D 2 O [58] guest proton donor molecules) and the proton affinity (151.1 kcal mol −1 vs. 143 kcal mol −1 [57] for CH 2 Cl 2 and 157.8 kcal mol −1 vs. 133 kcal mol −1 [57] for CHCl 3 ). Hunt and Andrews' estimate of the PA of CCl 4 as 130 kcal mol −1 is significantly lower than the G3 value of 167.2 kcal mol −1 calculated by Ma et al and also our PA estimate based on Hess law principles.…”
Section: Speciescontrasting
confidence: 64%
See 2 more Smart Citations
“…We used the standard G3 procedure [45] with the zero point energy corrected by using the HF frequency scaled by 0.8929, while Ma apparently used the MP2 frequencies scaled by 0.9661. However, our calculations (also Ma et al [39] and He and Wang's [49]) of the PAs of the chloromethanes at 298 K are significantly higher than the numbers quoted by Hunt and Andrews [57] and Holmes and Sodeau [58] who assumed a linear relationship between the frequency shift of the IR absorption (HF or D 2 O) bands for the entire chloromethane series (cold trapped in solid argon matrices with either HF, DF [57] or D 2 O [58] guest proton donor molecules) and the proton affinity (151.1 kcal mol −1 vs. 143 kcal mol −1 [57] for CH 2 Cl 2 and 157.8 kcal mol −1 vs. 133 kcal mol −1 [57] for CHCl 3 ). Hunt and Andrews' estimate of the PA of CCl 4 as 130 kcal mol −1 is significantly lower than the G3 value of 167.2 kcal mol −1 calculated by Ma et al and also our PA estimate based on Hess law principles.…”
Section: Speciescontrasting
confidence: 64%
“…Hunt and Andrews' estimate of the PA of CCl 4 as 130 kcal mol −1 is significantly lower than the G3 value of 167.2 kcal mol −1 calculated by Ma et al and also our PA estimate based on Hess law principles. The examination by us of the frequencies of the 5 and IR absorption bands of HF [57] and reported frequency shifts of the D 2 O absorption band [58] vs. the available G3 calculated PA values (from this work and Refs. [39,49]) for CH 2 Cl 2 , CHCl 3 , and CCl 4 (i.e., excluding the CH 3 Cl) showed excellent linear coefficient of > 0.9 for the frequency shift as a function of PA (the linear coefficient is drastically reduced by including CH 3 Cl).…”
Section: Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Adsorption of various organic molecules on ice surfaces can be described well with a multi-parameter linear free energy relationship, based on the van der Waals and the electron donor/acceptor interactions (such as H-bonding) (Roth et al, 2004 (Devlin, 1992;Devlin and Buch, 1995). Many organic halocarbon compounds have also been shown to adsorb on water-ices by interactions with the ice surface dangling bonds (Holmes and Sodeau, 1999). Studies of the adsorbed states of some organic molecules, such as acetonitrile, chloroform Roberts, 1999a, 1999b), acetone (Schaff and Roberts, 1998), or benzene derivatives (Borodin et al, 2004) have revealed the scope of hydrogen-bonding or dipolar interactions.…”
Section: Interaction Of Organics With Icementioning
confidence: 99%
“…siloxane bridges for silica or unsaturated surface oxygen atoms of ice. Dangling hydroxyl groups of water ice reveal slightly weaker frequency shifts on adsorption of weak bases, such as CO [13] or halogenated methanes [14]. In our case ethylene was tried as a base that could be put in contact with ice surface at 77 K, while the same CHF 3 and CO 2 were used as acids.…”
Section: Introductionmentioning
confidence: 92%